Preliminary analyses of natural radionuclides in selected Turkish power plant lignites - (:unkn) unknown (SPRINGER, 2004)
This preliminary study presents the experimental results concerning the concentrations of selected radionuclides (U-238, K-232, Ra-226, Tb-232) in Afsin-Elbistan, Can, Cayirhan, Erzurum, Goynuk, Kangal, Orhaneli, Saray, Seyitomer, Soma, Tuncbilek, Yatagan and Yenikoy lignites, which are primarily utilized as fuel for thermal power plants in Turkey. Gamma-spectrometry of 39 representative lignite samples gave results with the following concentration ranges: 8 to 296 Bq/kg for U-238, 3 to 79 Bq/kg for Th-232, 17 to 360 Bq/kg for K-40, and 5 to 130 Bq/kg for Ra-226. The U-238 results reported here are higher than other literature values for various world coals, earth's crust and world average.
Keywords: COAL; RADIOACTIVITY; ASHES